Serum IL-6 predicts immunotherapy-related adverse and outcome in advanced gastric and esophageal cancer patients with Anti-PD-1 treatment - Ma, Hongfang; Zhang, Shasha; Jiao, Pengqing; Ding, Haixia; Wang, Fujun; Zhao, Yue; Wu, Jianhua; Guo, Zhanjun (Frontiers in Immunology, 2025)
PurposeImmune checkpoint inhibitors (ICIs) significantly prolong the survival of cancer patients. including gastric adenocarcinoma (GAC) and esophageal squamous cell carcinoma (ESCC) patients. Immune-related adverse events (irAEs) are inevitably involved in ICIs treatment sometimes with severe consequences. Extreme caution is necessary for predicting irAEs and precisely screening of appropriate patients. We evaluated the association of interleukin-6 (IL-6) with irAEs and their impacts on ICIs treatment effectiveness in advanced GAC and ESCC patients.MethodsThis retrospective study analyzed 121 patients treated with ICIs between March 1, 2020 and August 31, 2023 to evaluate the association between serum IL-6 and ICIs treatment effectiveness. The occurrence of irAEs, including grade and category, and effectiveness of immunotherapy, including objective remission rate (ORR), disease control rate (DCR), progression-free survival (PFS) and overall survival (OS), was evaluated. Categorical count data were tested by chi-square test. Nonparametric rank sum tests were performed using Wilcoxon and Kruskal-Wallis test. Survival rate estimation and survival curves were generated using Kaplan–Meier curve and Log-rank test. Univariate and multivariable COX regression analyses were performed to identify independent prognostic factors.ResultsA total of 121 patients including 79 with GAC and 42 with ESCC patients were randomly divided into TC (n=81) and VC (n=40) groups. Higher serum IL-6 levels were associated with increased incidence of irAEs, the outcome analysis also indicated its association with lower DCR, shorter PFS and shorter OS in TC group. The higher IL-6 related irAEs occurrence and poor prognosis (DCR, PFS) was confirmed in the VC group. Individual tumor analysis showed that higher IL-6 was associated with both irAEs occurrence and poor prognosis (DCR, PFS, OS) in ESCC patients, and with irAEs occurrence and poor prognosis (DCR, PFS) in GAC patients. No statistically significant associations were observed between pathological biomarkers including programmed cell death ligand 1 (PD-L1), mismatch repair (MMR) and human epidermal growth factor receptor 2 (HER2) and either IL-6 levels or irAEs occurrence in both GC and ESCC patients.ConclusionElevated serum IL-6 levels were associated with the incidence of irAEs, and higher IL-6 levels predicted worse prognosis in GAC and ESCC patients with ICIs treatment.